FAKTOR YANG MEMPENGARUHI PEMBIAYAAN BAGI HASIL PADA BANK UMUM SYARIAH DI INDONESIA - Sasma Aprilia; Dewa P. K Mahardika (JRAK, 2019)
This research is conducted to measure that the capital adequacy ratio, non performing financing, and third party fund give impacts on financing of profit sharing, either simultaneously or partially. This research is a causal descriptive verification research. Unit of analysis in this research is sharia banks in Indonesia. The research data were collected by purposive sampling technique which include 7 Islamic banking that have been running for six years, in the period of 2011-2016. This study uses panel data regression. The results showed that the capital adequacy ratio, non performing financing, and third party fund simultaneously give influence to the financing of profit sharing. Partially, the capital adequacy ratio and non-performing financing does not affect the financing of profit sharing. while third party fund deposits have a positive effect on the financing of profit sharing.